The Impact of Physical Activity on Premenstrual Syndrome in Female Students at the Faculty of Medicine, Tarumanagara University - Carin, Carin; Wahyuni , Octavia Dwi (Universitas Islam Negeri Alauddin Makassar, 2026)
Background: Premenstrual syndrome (PMS) is a common disorder among women of reproductive age that can disrupt daily activities and quality of life. Various factors, including physical activity, may influence the incidence and severity of PMS. However, limited studies focus on medical students, a group with high academic demands and potentially unbalanced physical activity. Objective: To analyze the relationship between physical activity level and the incidence and severity of PMS among female students of the Faculty of Medicine, Universitas Tarumanagara. Methods: This was an analytical observational study with a cross-sectional design conducted at the Faculty of Medicine, Universitas Tarumanagara, from December 2024 to February 2025. A total sampling approach was used, involving 233 female students; after exclusions, 226 respondents (aged 17–24 years) were included. Data on physical activity (IPAQ) and PMS symptoms (SPAF) were collected via questionnaires and analyzed using the chi-square test. Results: Most respondents reported engaging in light physical activity (71.2%). PMS was more frequent and severe among those with light activity (21.7% severe PMS) compared to moderate (14.0% severe) and heavy activity (4.5% severe, majority asymptomatic). Statistical analysis showed a significant relationship between physical activity level and PMS incidence and severity (p=0.004). Conclusion: Higher levels of physical activity (moderate to heavy) are associated with a reduced risk and severity of PMS symptoms among female medical students. Routine physical activity is recommended to support reproductive health.